Reduced uterine volume after induction of puberty in women with hypogonadism. (9th October 2019) - Burt, Elizabeth; Davies, Melanie C.; Yasmin, Ephia; Cameron‐Pimblett, Antoinette; Mavrelos, Dimitri; Talaulikar, Vikram; Conway, Gerard S.
Abstract: Objective: Adequate uterine growth is an essential component of pubertal induction with exogenous oestradiol in those with hypogonadism. Poor uterine development will render the individual vulnerable in the context of fertility. We assessed uterine size using ultrasound in those who had undergone pubertal induction treatment compared with a reference group who had experienced spontaneous puberty. Design: This is a single‐centre, retrospective, cross‐sectional study of women who underwent pubertal induction compared with a reference group. Patients: Ninety‐five women with hypogonadism who had previously undergone pubertal induction and were receiving maintenance oestrogen replacement as adults were recruited: 48 women with Turner syndrome, 32 with premature ovarian insufficiency and 15 with gonadotrophin deficiency. The reference group consisted of 35 nulliparous women attending with male factor subfertility with a normal pelvis on ultrasonography. Measurements: Pelvic ultrasound was performed by a single observer. Uterine dimensions (total length, anterior–posterior (AP), transverse, uterine volume and fundal cervical AP ratio (FCR) measurements) were recorded. Clinical details were also recorded. Results: Those with hypogonadism had significantly reduced uterine dimensions compared with the reference group (uterine length 64 mm vs 71 mm P  = <.05, uterine volume 28.9 mL vs 43.9 mL P  = <.05). All women in the reference group attained a mature uterine configuration with a FCR >1, compared with 84% of those with hypogonadism ( P  = .01). A total of 24% and 48% of the diagnostic group had total uterine length and uterine volume measurements less than the 5th percentile of the reference group, respectively. In a subgroup of 22 women in whom serum oestradiol concentrations could be analysed, there was a positive correlation between this parameter and uterine volume. Conclusion: Despite standard oestrogen therapy, uterine growth is often compromised in those with hypogonadism. Uterine health has historically been overlooked in pubertal induction protocols; however, with increasing options for fertility treatment, adequate uterine development is crucial. Given the variation in uterine size witnessed, a more tailored approach to treatment with regular monitoring of uterine dimensions should be advocated.